Freedom To Act Dalam Perspektif Ekonomi Syariah (Studi Prospek Ekonomi Syariah Era 4.0 di Indonesia) - Ilyas Nurul Azam; Kurniatiningsih, Eka (J-Mabes: Jurnal Manajemen, Akuntansi, Bisnis dan Studi Ekonomi Syariah, 2023)
Economic freedom is a form of freedom or authority possessed by individuals of each economic actor to carry out economic activities with all the capabilities, opportunities and desires they have in their efforts to meet life needs and satisfaction with the ultimate goal of welfare level. Since the development of the Industrial Revolution from era 1.0 to 4.0, there have been various developments towards regenerating the industry in a direction that is completely sophisticated, both in information technology and communication technology. This era of 4.0 is not well understood and implemented by the majority of countries in the world. This is due to a lack of knowledge and the inability of a country to keep up with the very rapid pace of industrial development in the 4.0 era. This research, it is intended that the prospect study of the sharia economy can contribute to a country, especially Indonesia, so that it can keep up with the pace of economic development in the 4.0 era, so that the lack of relevance of the 4.0 era can be addressed by the transformation of the sharia economic prospects. This case, the author uses qualitative research methods with the type of literature (library research) wich uses a theological-philosophical approach directed at universal coclusions with a fulcrum at the root of the problem. The produces research on the point of relevance of the sharia economic prospects in addressing the pace of economic freedom in the era of 4.0 which is considered irrelevant in the majority of countries in the world. As for the point that is considered relevan in islamic economics is the point of utility, equality of opportunity, social justice, multiple ownership and others.